Validity of CELL Model to Nurturing Student’s Ethnoscience Literacy and Collaborative Skill - Shofatun, Anis; Agustini, Rudiana; Rahayu, Yuni Sri (IKIP Widya Darma Surabaya, 2026)
Objectives: Ethnoscience literacy learning trains students to understand and solve complex problems with a holistic, culture-based approach. Collaborative skills prepare students to work in teams to face the challenges of interconnected life in the 21st century. Previous research found that students' scientific literacy competencies and collaboration skills in several regions in Indonesia still need improvement. Scientific literacy integrated local wisdom and students' socio-emotional skills. Learning interventions are needed to prepare students to face global challenges. This study aims to validate the CELL learning model. Method: Educational development research was used as the research design, involving two criteria: content validation and construct validation. Three experts in the fields of pedagogy, science content, and learning assessment validated the CELL learning model. Results: The research results and data analysis indicated that the CELL learning model has consistently provided relevant results. The CELL model has met strict validity and reliability standards (with an agreement percentage >75%). Novelty: Validated learning support components includes lesson plans, student textbooks, student worksheet, ethnoscience literacy tests and collaborative skills. The CELL learning model can be applied to train students' ethnoscience literacy competencies and collaborative skills by integrating science with local wisdom and students' socio-emotional development. The CELL learning model is suitable for meaningful science learning and developing students' social skills.